2022
DOI: 10.1002/fsn3.3157
|View full text |Cite
|
Sign up to set email alerts
|

Anemia in children aged 6–59 months was significantly associated with maternal anemia status in rural Zimbabwe

Abstract: Globally, anemia is a public health problem affecting mostly women of reproductive age (WRA, n = 452) and children aged 6-59 months (n = 452) from low-and lowermiddle-income countries. This cross-sectional study assessed the prevalence and determinants of anemia in WRA and children aged 6-59 months in rural Zimbabwe.The venous blood sample was measured for hemoglobin utilizing a HemoCue machine. Anthropometric indices were assessed and classified based on World Health Organization standards. Socioeconomic char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…Economic conditions play a significant role in influencing nutritional anemia, where lower income is associated with higher prevalence. A notable difference in the prevalence of first quartile income was observed compared to the control group, consistent with existing literature ( 23 , 24 ). This phenomenon could potentially be attributed to the limited access to healthy food in areas where economically disadvantaged and vulnerable populations reside ( 25 , 26 ).…”
Section: Discussionsupporting
confidence: 91%
“…Economic conditions play a significant role in influencing nutritional anemia, where lower income is associated with higher prevalence. A notable difference in the prevalence of first quartile income was observed compared to the control group, consistent with existing literature ( 23 , 24 ). This phenomenon could potentially be attributed to the limited access to healthy food in areas where economically disadvantaged and vulnerable populations reside ( 25 , 26 ).…”
Section: Discussionsupporting
confidence: 91%
“…Recruitment was done at the household level, with participants then directed to the nearest health facility for data collection. Additional information on the sampling design is described in Mutonhodza et al ( 70 ).…”
Section: Methodsmentioning
confidence: 99%
“…A study by Kothari et al found mixed findings on the associations between the water source and anaemia in the analysis of 47 demographic and health surveys [ 76 ]. However, only some studies conducted in Zimbabwe [ 77 ] and Liberia [ 78 ] found a significant association between the use of unimproved sources of drinking water and anaemia in children. These conflicting findings may result from various infectious disease pathogens in various environments, dietary patterns, and other behavioural factors related to water handling and treatment that may influence the relationship between anaemia and the household water source.…”
Section: Discussionmentioning
confidence: 99%